KEPENTINGAN INDONESIA BEKERJASAMA DENGAN “REGIONAL PLAN OF ACTION TO PROMOTE RESPONSIBLE FISHING PRACTICES INCLUDING COMBATING IUU FISHING IN THE SOUTHEST ASIA REGION” ( RPOA – IUU ) TAHUN 2016 - Muhammad Hibatul Azis; Faisal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to understand what is the national interest of Indonesia to join RPOA in 2016. As an archipelago county, Indonesia has a huge potential of natural resources in particulary maritime sector. In addition, Indonesia consist of 30% land capacity and 70% sea wider. Therefore, Indonesia has always been an object of illegal fishing through their maritime land. Apparently, Indonesia isnt the only one that concern into maritime security, ASEAN or regional countries have put their attention to solve those problems such Illegal fishing that reducing their own fish stock. So, 11 countries in regional made a cooperation under RPOA to combating illegal fishing. Thus researcher question is what is Indonesia National Interest In A Cooperation With Regional Plan Of Action To Promote Responsible Fishing Practices Including Combating Iuu Fishing In The Southeast Asia Region” (Rpoa – Iuu) In 2016.This research theoretically has built with realism perspectives on International Relations and supported by Foreign Policy theory K.J. Holsty. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Indonesia national interest to join RPOA is caused Indonesia wants to guard and secure their own of maritime land particularly in ALKI (Alur Laut Kepulauan Indonesia) whic Indonesia as archipelago country has been loss on profit towards illegal fishing.Keywords : National Interest, Indonesia, Cooperation, Illegal Fishing, RPOA, ALKI